The impact of benevolent leadership and workplace friendship on job satisfaction through job involvement - Wang, Shaodan (2021)
Due to the dynamic nature of the global environment, organizations face some challenges in modern society. One of the many challenges that companies face is to satisfy their employees to adapt to a constantly evolving and changing environment and to achieve success and maintain a competitive advantage. To improve employee effectiveness, efficiency, work commitment, and productivity, corporates must meet and satisfy the needs of employees by adopting effective leadership and focus on the relationships at the workplace. The objective of this paper is to analyze the impact of benevolent leadership and friendship at work on employee job satisfaction through job involvement. The study adopted a quantitative methodology. Primary data was collected through self-managed online questionnaires. The questionnaire is taken from several previous articles. The target population consists of employees and employers from China. Simple random sampling is used to collect data from 263 participants. The results indicate a positive relationship between benevolent leadership and employee job satisfaction through job involvement, while friendship at the workplace has no significant effect on job satisfaction through job involvement. The study concludes with some brief prospects that companies and managers need to recognize the importance of benevolent leadership in maximizing the level of employees’ job satisfaction. This paper may contribute to employees’ personal growth and development by encouraging managers to motivate employees with benevolence for achieving organizational goals and improve job involvement and job satisfaction to make more achievements to their work and society.